NEEDLE CHANGING AND OCCURRENCE OF LOCAL ADVERSE EFFECTS AFTER HB VACCINATION - M. Payami Boosari; N. Mosavinasab (Iran University of Medical Sciences, 2004)
Health professionals for adminstering intramascular (IM) injections use two usual techniques. First of all the injectable is drawn up, using a needle which is then changed with a new one before administration. The other is using one needle for both drawing and injecting drugs. It is supposed that the first method would reduce pain, swelling and redness of the injection site after immunizing with Hepatitis B Vaccine (HBV). So, in order to determine the differences between these two methods, a controlled trial study was conducted, in which 39 nursing students were selected randomly to participate as the sample group and were assigned in two groups for the first and the second methods, and a follow up program was designed to check the injection site during four days. Results showed that changing of the needle would reduce redness and swelling meaningfully, with the respectively P Values of (0.04) and (0.03), and the rates of tenderness and pain were also lower in two needle technique, although, it was not significantly meaningful. To conclude, the use of two-needle technique significantly reduced local reactions in routine immunization of adult's. So, immunization centers should review their policy of changing needle before administration of vaccines.